Preclinical characterization of tunlametinib, a novel, potent, and selective MEK inhibitor - Liu, Yahong; Cheng, Ying; Huang, Gongchao; Xia, Xiangying; Wang, Xingkai; Tian, Hongqi (Frontiers in Pharmacology, 2023)
Background: Aberrant activation of RAS-RAF-MEK-ERK signaling pathway has been implicated in more than one-third of all malignancies. MEK inhibitors are promising therapeutic approaches to target this signaling pathway. Though four MEK inhibitors have been approved by FDA, these compounds possess either limited efficacy or unfavorable PK profiles with toxicity issues, hindering their broadly application in clinic. Our efforts were focused on the design and development of a novel MEK inhibitor, which subsequently led to the discovery of HL-085 (Tunlametinib). Methods: This study verified the superiority of HL-085 over the current MEK inhibitors in preclinical studies. The protein kinase selectivity activity of HL-085 was evaluated against 77 kinases. Anti-proliferation activity was analyzed using the 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) or (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) (MTS) assay. ERK and phospho-ERK levels were evaluated by Western blot analysis. Flow cytometry analysis was employed to investigate cell cycle and arrest. Cell-derived xenograft (CDX) and Patient-derived xenograft (PDX) models were used to evaluate the tumor growth inhibition. The efficacy of HL-085 as monotherapy treatment was evaluated in KRAS/BRAF mutant or wild type xenograft model. Furthermore, the combination studies of HL-085 with BRAF/KRASG12C/SHP2 inhibitors or chemotherapeutic agent were conducted by using the cell proliferation assay in vitro and xenograft models in vivo. Results: In vitro, HL-085 demonstrated high selectivity with approximately 19-fold greater potency against MEK kinase than MEK162, and nearly 10-100-fold greater potency against RAS/RAF mutant cell lines than AZD6244. In vivo, HL-085 resulted in dramatic tumor suppression and profound inhibition of ERK phosphorylation in tumor tissue. Mechanistic study revealed that HL-085 induced cell cycle arrest at G0/G1 phase and apoptosis of cells in a dose-proportional manner. In addition, HL-085 demonstrated a favorable pharmacokinetic profile with dose-proportionality and good oral bioavailability, with minimal drug exposure accumulation. Furthermore, HL-085 combined with BRAF/KRASG12C/SHP2 inhibitors or docetaxel showed synergistically enhanced response and marked tumor inhibition. Conclusions: HL-085 exhibited a promising approach for treating RAS/RAF mutant cancers alone or as combination therapies, supporting the evaluation in clinical trials. Currently, the first-in-human phase 1 study and pivotal clinical trial of HL-085 as monotherapy have been completed and pivotal trials as combination therapy are ongoing.